Geology Paleoclimatology and Paleoenvironment analysis using plant fossils at Paya Peda, Besut, Terengganu - Nik Ahmad Ikhwan Pauzi (2016)
A large collection of plant fossils is discovered from a sequence of shale and slate along the road cutting outcrop at Paya Peda Dam construction site in Besut, Terengganu. This study area is located at 5°34’47"N and 102°31 '16"E. The objectives of the research are to update the geological map of the study area with the scale of 1:25 000, to identify the plant fossils existed and to interpret the paleoclimate and paleoenvironment of the study area. Geological mapping is conducted to identify the stratigraphy and structural geology of the study area besides petrography is done to analyze the composition of mineral in the rock samples. Plant fossils are then identiﬁed based on their taxonomy in order to interpret the paleoclimate and paleoenvironment of the study area. As a result, Paya Peda is a part of Telemong Formation which covers the lithology of sandstone, mudstone, shale, slate and homfels. The plant fossils assemblage consists of Cordaites sp., Archaeoptoris sp., Pecopteris sp. and Neuropteris sp. These plant fossils are dated in Carboniferous Period where it experienced tropical condition on the past climates and characterized by both shallow marine on the past environments. In a nutshell, protection of Paya Peda area can help the plant fossils to be preserved as the authenticity of the fossils can remain permanent together.